The Development of Emporia Digital Raya's "IKI Canvasser" Stores Acquisition Mobile Application - Arciliyagutama, Billy Alvin; Widiantoro, Albertus Dwi Yoga; Prasetya, FX Hendra (Journal of Business and Technology, 2023)
Inequity technology development in Indonesia had a bad impact on micro and small local stores all over Indonesia. This condition made Emporia Digital Raya acquire micro and small local stores as digital store partners to boost up their income. In a way to fasten the process, Emporia Digital Raya developed a mobile application to help and fasten the Acquirer (Emporia Digital Raya call it Area Leader) process in acquisition. This journal explains how this application is developed in the form of a mobile application based on Area Leader needs like acquisition, supervise store performance, and store visit report. This research was conducted with a quantitative method. The data collection is done by survey and literature study. Mobile application development is carried out using Java, Codeigniter 2 as the Application Programming Interface or API, PostgreSQL as database server, and Apache as the server. The study shows an overall result that this application is useful in helping Area Leaders to acquire and supervise their stores. This application is also considered user friendly. The results of application testing have been confirmed to pass the quantitative test using a survey method with 100 Area Leader from all over Indonesia.